2004
DOI: 10.1111/j.1600-6143.2004.00438.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of an ABO-Incompatible Lung Transplant

Abstract: The treatment regimen that we adopted may prove useful in other cases of unplanned ABO-incompatible organ transplants. The successful outcome suggests that planned ABO-incompatible lung transplants may be possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…However, blood group O recipients have pre-existing natural antibodies against the "A" and "B" antigens (hemaglutinins) and so can only receive organs from group O donors because of a risk of hyperacute (antibody-mediated) rejection of A and B organs. 1,12 Therefore, on each occasion that a blood group O donor heart is used for a non-O patient, the number of hearts available to group O patients is reduced. The reasons given for offers of blood group A and B donor hearts not resulting in transplant suggest that some of these organs could have been used in blood-group-identical patients, freeing up some group O hearts for use in group O recipients.…”
Section: Discussionmentioning
confidence: 99%
“…However, blood group O recipients have pre-existing natural antibodies against the "A" and "B" antigens (hemaglutinins) and so can only receive organs from group O donors because of a risk of hyperacute (antibody-mediated) rejection of A and B organs. 1,12 Therefore, on each occasion that a blood group O donor heart is used for a non-O patient, the number of hearts available to group O patients is reduced. The reasons given for offers of blood group A and B donor hearts not resulting in transplant suggest that some of these organs could have been used in blood-group-identical patients, freeing up some group O hearts for use in group O recipients.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Rituximab has also been described as an important adjunct component of rescue therapy after inadvertent ABO-incompatible lung transplantation. 21,22 To date, 4 case reports have been published describing the successful handling of humoral rejection episodes coming along with hemodynamic compromise after of cardiac transplantation. Garrett et al, 23 Aranda et al, 24 Baran et al, 25 and Keren et al 26 each successfully treated a patient with a hemodynamically significant rejection episode refractory to conventional therapy with the administration of anti-CD20 monoclonal antibody.…”
Section: Discussionmentioning
confidence: 98%
“…PRA reduction was generally incomplete and cross-matches remained positive at transplant, but graft dysfunction was not observed in the two lung allograft recipients, who died of CMV (7 months) and obliterative bronchiolitis (N 4 years). The Harefield case, where ABO-incompatible graft injury was not seen despite an anti-A titer of 1:256 [13], and a Minnesota case [34], where anti-HLA A2-associated HAR was apparently reversed, indicate that immediate plasmapheresis with selective or non-selective reduction in titer of pathogenic antibodies is a rational approach to prevent humoral graft injury in this circumstance. These cases and our Vanderbilt experience indicate that accommodation and antigen-specific tolerance can occur, although the conditions required to accomplish this remain uncertain.…”
Section: Antibody-induced Lung Injury: Theoretical and Experimental Cmentioning
confidence: 93%
“…The patient developed evidence of both graft accommodation and antigen-specific immunomodulation, and lived for over 4 years before succumbing to acute-on-chronic respiratory insufficiency and multisystem organ failure of uncertain pathogenesis. Banner et al reported a successful outcome after inadvertent ABO-incompatible lung transplant [13]. An A-to-O bilateral lung recipient with a high anti-A titer (1:256) was treated with intraoperative plasmapheresis followed by non-antigen-specific immunoadsorption, IVIg and anti-CD20.…”
Section: Case Reportsmentioning
confidence: 98%